2005
DOI: 10.4049/jimmunol.175.9.5708
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Uteroglobin-Related Protein 2 (Ugrp2) Gene Expression by the Th2 Cytokines IL-4 and IL-13

Abstract: Uteroglobin-related proteins 1 and 2 (UGRP1 and -2) are thought to play important roles in inflammation and immunologic responses in the lung. In this study we demonstrate that IL-4 and IL-13 enhance Ugrp2 gene expression in the mouse transformed Clara cell line, mtCC, in a time- and dose-dependent manner. Addition of actinomycin D abrogated the IL-4- and IL-13-induced increase of Ugrp2 expression, demonstrating that this increase occurs at the transcriptional level. When mtCC cells were pretreated with IFN-γ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…Moreover, several reports have described the modulation of gene expression in Clara cells by the Th2 cytokines IL-4 and IL-13 [33,34]. Ablation of nuclear factor-kB signalling in Clara cells reduces peribronchial fibrosis, CD4+ cell infiltration, airway mucus, CCL17 and eotaxin release and eosinophils in allergen-challenged mice [34,35]. Together, these and other studies demonstrate that epithelial cells have the ability to respond and orchestrate lung immune responses.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, several reports have described the modulation of gene expression in Clara cells by the Th2 cytokines IL-4 and IL-13 [33,34]. Ablation of nuclear factor-kB signalling in Clara cells reduces peribronchial fibrosis, CD4+ cell infiltration, airway mucus, CCL17 and eotaxin release and eosinophils in allergen-challenged mice [34,35]. Together, these and other studies demonstrate that epithelial cells have the ability to respond and orchestrate lung immune responses.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, the expression of pattern recognition receptors, such as Toll-like receptor 4, on the lung epithelium has a critical role for the activation of dendritic cells (DC) in allergic lung inflammation, stressing the importance of the lung tissue microenvironment for efficient Tcell activation [32]. Moreover, several reports have described the modulation of gene expression in Clara cells by the Th2 cytokines IL-4 and IL-13 [33,34]. Ablation of nuclear factor-kB signalling in Clara cells reduces peribronchial fibrosis, CD4+ cell infiltration, airway mucus, CCL17 and eotaxin release and eosinophils in allergen-challenged mice [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This core palindromic sequence matches the consensus sequence for DNA binding used by all of the Stat transcription factors, including Stat6 and Stat1. Recently, Yamada et al (30) found that both Stat1 and Stat6 bind to the same Stat factor binding element in the promoter of the IL-4-and IL-13-responsive Ugrp2 gene and that activation of Stat1 decreased the binding of Stat6 to the site. One mechanism to explain our findings of the opposing effects of Stat1 and Stat6 on IL-13-induced PDGF-A and PDGF-C is that there exists a competition between Stat1 and Stat6 for binding to the Stat factorbinding element in the Egr-1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…A double-stranded oligonucleotide (21 nt) probe was prepared based on the STAT-binding DNA sequence present in the mouse Ugrp2 gene promoter (12), and used as a probe in the gel-shift assays. Binding reactions were performed at room temperature for 30 minutes by incubating radiolabeled probe DNA (.…”
Section: Electrophoretic Mobility Shift Analysismentioning
confidence: 99%
“…Involvement of the AKT pathway is also implicated in epidermal growth factor (EGF) and transforming growth factor (TGF)-a-induced SCGB3A1 expression (11). Further, the Th2 cytokines IL-4 and IL-13 induce SCGB3A1 expression, suggesting that this gene may potentially play a role in the pathogenesis of inflammatory lung diseases (12). In this respect, the involvement of SCGB3A2, a homologous gene to SCGB3A1, in lung inflammation has been described; proinflammatory cytokines IL-5 and IL-9 reduce SCGB3A2 expression (13,14), whereas anti-inflammatory cytokine IL-10 enhances expression (15).…”
mentioning
confidence: 99%